Colloidal synthesis of Y-doped SnO2 nanocrystals for efficient and slight hysteresis planar perovskite solar cells. (June 2019) - Song, Jing; Zhang, Weina; Wang, Deng; Deng, Kaiming; Wu, Jihuai; Lan, Zhang
Graphical abstract: Highlights: High-quality SnO2 ETLs are prepared with colloidal synthesized Y-SnO2 NCs. Optimized energy level and electron-transport dynamics of SnO2 ETLs are achieved by Y doping. PSCs employing Y-SnO2 ETLs achieve a champion efficiency as high as 20.71%. Abstract: It is well known that the electron-transporting layers (ETLs) play an indispensable role in any types of high efficient perovskite solar cells (PSCs) because of their important functions in extracting/transporting electrons and blocking holes during the light-to-electricity conversion process. High quality ETLs are necessary for preparing efficient planar PSCs because the electron diffusion length is shorter than its hole counterpart in perovskite materials and the planar PSCs have short electrons extracting channels due to the lack of mesoporous layers. Recently, impressive advances in planar PSCs with SnO2 ETLs have been reported due to the perfect characteristics of SnO2 material including suitable energy level, high electron mobility, good transmittance, excellent chemical stability, inactive UV photocatalysis, and so on. Here, we use the doping route to further enhance the quality of SnO2 ETLs. The SnO2 nanocrystals are doped with Y 3+ through the typical solvothermal method. The Y dopant leads to more suitable energy level structure and better charge carrier dynamics in the devices than those of the undoped ones. The planar PSCs with Y-SnO2 ETLs achieve a champion efficiency of 20.71% with slight hysteresis, much higher than the undoped ones (18.08%).